Attenuating Cholinergic Transmission Increases the Number of Satellite Cells and Preserves Muscle Mass in Old Age - Vaughan, Sydney K.; Sutherland, Natalia M.; Valdez, Gregorio (Frontiers in Aging Neuroscience, 2019)
In addition to driving contraction of skeletal muscles, acetylcholine (ACh) acts as an anti-synaptogenic agent at neuromuscular junctions (NMJs). In this study, we hypothesized that moderately and chronically reducing ACh could attenuate the deleterious effects of aging on NMJs and skeletal muscles. To test this hypothesis, we analyzed NMJs and muscle fibers from heterozygous transgenic mice with reduced expression of the vesicular acetylcholine transporter (VKDHet), which present with approximately 30% less synaptic ACh compared to control mice. Because ACh is constitutively decreased in VKDHet, we first analyzed developing NMJs and muscle fibers. We found no obvious morphological or molecular differences between NMJs and muscle fibers of VKDHet and control mice during development. In contrast, we found that moderately reducing ACh has various effects on adult NMJs and muscle fibers. VKDHet mice have significantly larger NMJs and muscle fibers compared to age-matched control mice. They also present with reduced expression of the pro-atrophy gene, Foxo1, and more satellite cells in skeletal muscles, two molecular and cellular features that may partially explain the increased size of NMJs and muscle fibers. These and other data in this manuscript indicate that moderately reducing ACh may be a therapeutic strategy to prevent the loss of skeletal muscle mass that occurs with advancing age.